The Voices of Minority Students in an Agricultural Communications and Journalism Program: A Case Study - Rebecca McGovney-Ingram; Tracy Rutherford; Alvin Larke Jr. (Journal of Applied Communications, 2011)
In 1998, the National Association of State University and Land Grant Colleges addressed the “access challenge” for minority students, stating nothing less than open opportunity and commitment would embrace the land grant history. Researchers have documented barriers and strategies for the recruitment and retention of minority students in agricultural education. The experiences minority students have in college are unique, and effective recruitment and retention strategies should only be developed after in-depth, explorative conversations with the students; therefore, the purpose of this study was to begin the dialogue with minority students in agricultural communications. Nine students, eight female and one male were interviewed for this qualitative case study. This research was framed by the following questions: (1) Who are minority students within the predominantly White agricultural communications and journalism program at a southern university, (2) What are the experiences of minority students within the predominantly White agricultural communications and journalism program at a southern university, and (3) What are the perceptions of minority students of the predominantly white agricultural communications and journalism program at a southern university.
Keywords: Land Grant Colleges; minority; dialogue; backgrounds; education; communications